Preparation of Fe–N–C catalysts with FeNx (x = 1, 3, 4) active sites and comparison of their activities for the oxygen reduction reaction and performances in proton exchange membrane fuel cells. Issue 45 (8th November 2019) - Li, Yongcheng; Liu, Xiaofang; Zheng, Lirong; Shang, Jiaxiang; Wan, Xin; Hu, Riming; Guo, Xu; Hong, Song; Shui, Jianglan
Abstract : The active sites of Fe–N–C catalysts are nitrogen coordinated iron atoms, FeN x ( x = 1–5), that have five possible coordination numbers, corresponding to different ORR activities and PEMFC performances. Abstract : The active sites of Fe–N–C catalysts are nitrogen coordinated iron atoms, FeN x ( x = 1–5), that have five possible coordination numbers. FeN4 active sites are commonly reported, but active sites with other coordination numbers are rarely prepared and compared with FeN4 for the oxygen reduction reaction (ORR) in proton exchange membrane fuel cells (PEMFCs). Herein, Fe–N–C catalysts with different coordination numbers but similar active site densities are synthesized. Combined with theoretical calculations, the effects of FeN x coordination number x on the ORR activity and PEMFC performance are systematically investigated. It is found that the annealing temperature is the key to tailoring the coordination number of FeN x . The ORR activity and PEMFC performance follow the order FeN4 > FeN3 > FeN1 . FeN4 delivers almost 1.7× and 2.9× peak power densities, and 2× and 14× current densities (at 0.7 V) compared with FeN3 and FeN1, respectively. Theoretical calculations demonstrate an "inverted volcano" relationship for the formation energy and a "volcano" relationship for the ORR activity as a function of coordination number x = 1–5. FeN4 was proved to have the lowest formation energy, the highest ORR activity and the best PEMFC performance among the five types of FeN x ( x = 1–5). This research provides a deep insight into the differences among FeN x active sites of Fe–N–C catalysts.